An Ab Initio Electronic Structure Investigation of the Ground and Excited States of ScH+, YH+, and LaH+ - Isuru R. Ariyarathna (Molecules)
Multireference configuration interaction (MRCI), Davidson-corrected MRCI (MRCI+Q), coupled-cluster singles, doubles, and perturbative triples [CCSD(T)], and frozen-core full configuration interaction (fcFCI) calculations were carried out using large, correlation-consistent basis sets to investigate the excited states of the Sc atom and the spin–free and spin–orbit coupled potential energy profiles, energetics, spectroscopic constants, and electron populations of low-lying states of MH+ (M = Sc, Y, La). The core electron correlation effects, complete basis set effects, and spin–orbit coupling effects were also evaluated. The first four electronic states of all MH+ are 12Δ, 12Σ+, 12Π, and 22Σ+ with 1σ21δ1, 1σ22σ1, 1σ21π1, and 1σ23σ1 single-reference electron configurations, respectively. These states of MH+ can be represented by the M2+H– ionic structure. The ground states of ScH+, YH+, and LaH+ are 12Δ3/2, 12Σ+1/2, and 12Δ3/2 with 55.45, 60.54, and 62.34 kcal/mol bond energies, respectively. The core electron correlation was found to be vital for gaining accurate predictions on the ground and excited state properties of MH+. The spin–orbit coupling effects are minor for ScH+ but become substantial moving to YH+ and LaH+. Overall, the results of this work are in good agreement with the limited set of experimental findings of MH+ available in the literature and will be of use for future investigations. Furthermore, the theoretical approaches, findings, and trends reported here are expected to aid studies of similar species.